Targeting EGFR and ALK in NSCLC: current evidence and future perspective. (June 2016) - Bennati, Chiara; Paglialunga, Luca; Ricciuti, Biagio; Metro, Giulio; Marcomigni, Luca; Gili, Alessio; Crinò, Lucio
The advent of molecular therapy targeting specific driver oncogenes has dramatically changed the prognosis of a subset of NSCLC, dilating survival and improving the quality of life of patients with advanced disease. Two of the major targets for treatment with receptor TKIs are the activated mutated forms of the EGFR and the ALK gene fusions. In advanced NSCLC patients harboring EGFR mutations or ALK rearrangements, the use of TKIs in the first-line setting, have provided unexpected large progression-free survival and overall survival benefits, compared with cytotoxic chemotherapy. However, despite initial responses and durable remissions, the development of resistance inevitably leads to treatment failure. The aim of this review is to discuss the treatment strategy currently used for tumors harboring these two genetic targets and to focus on what will be available in clinical practice in the near future.